2017
DOI: 10.1167/iovs.17-22345
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous Fibronectin and Fibrinogen Expression Increased in Eyes With Proliferative Diabetic Retinopathy After Intravitreal Anti-VEGF Therapy

Abstract: PURPOSE. To evaluate vitreous humor (VH) protein expression profiles in patients with proliferative diabetic retinopathy (PDR), with and without intravitreal injection (IVI) of antivascular endothelial growth factor (anti-VEGF) before vitrectomy. METHODS.We enrolled consecutive PDR patients who needed pars plana vitrectomy (PPV) with or without IVI or pan-retinal photocoagulation (PRP). Visual acuity, duration, and treatment of diabetes mellitus, ocular treatment history, and fundus examinations were recorded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 40 publications
(43 reference statements)
0
25
0
Order By: Relevance
“…; Wei et al. ). Randomized control trials for the timing of preoperative anti‐VEGF injection in vitrectomy for eyes with PDR should be needed.…”
Section: Discussionmentioning
confidence: 98%
“…; Wei et al. ). Randomized control trials for the timing of preoperative anti‐VEGF injection in vitrectomy for eyes with PDR should be needed.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have found that anti-VEGF therapy could improve diabetic nephropathy and retinopathy [6, 7]. However, in recent years, more and more basic and clinical studies have found that anti-VEGF might lead to proteinuria [8], deterioration of renal disease, and renal thrombotic microvascular disease [9], and there was no clinical improvement in most patients with retinopathy [10]. This indicates that a certain amount of VEGF is required to maintain organ function in physiological state.…”
Section: Introductionmentioning
confidence: 99%
“…Obeid et al, 2019(Obeid et al, 2019 further investigated 59 PDR patients who were LTFU for over 6 months, in which anti-VEGF monotherapy manifested worse anatomic and functional outcomes. Wei et al (2017) also reported that fibronectin and fibrinogen concentrations in vitreous humor of intravitreal anti-VEGF injection group, which might promote fibrosis in eyes with PDR. Thus, many problems of anti-VEGF therapy remain to be solved.…”
Section: Discussionmentioning
confidence: 89%